E-Banking Technology: A Comprehensive Study on Customer Satisfaction and Bank Services - Dewi, Cynthia Sari; Zulkifli, Zulkifli (IJBLE Scientific Publications Community Inc., 2024)
This paper explores the dynamic landscape of e-banking technology, emphasizing advancements in hardware, software, and networks to deliver innovative solutions. It highlights moderate e-banking adoption among surveyed individuals, underscoring the crucial role of customer satisfaction in banking services. Despite this, critical gaps are identified, motivating the study to provide a detailed analysis of responses concerning cloud services, bank system security, service quality, and e-learning initiatives. With meticulous data collection from 125 respondents, primarily students from Tangerang actively using e-banking, the research investigates the frequency and patterns of e-banking usage. Through comprehensive descriptive analysis, the study offers insights into customer satisfaction in the e-banking domain and sets the stage for future causal research. Its ultimate goal is to enhance comprehension of the factors influencing customer satisfaction in e-banking.